Fiscal Decentralization Practices in Federal System: An Evidence from Some Countries and Western Hill, Nepal - Silwal, Sudarshan (International Research Journal of MMC, 2025)
This paper examines the fiscal decentralization practices of some federal countries and perception from public regarding the overall federal system in Western hill of Dhawalagiri region selecting Baglung municipality, Beni municipality and Kusma municipality as a sample purposively from Gandaki Province of Nepal. This research work follows a mixed methods approach. For this, available literature as a secondary sources are reviewed from abroad countries adopted federal system into practice. Similarly, for assessing the perception of respondents regarding the issues such as institutional powers, people truest in the overall system, inter-governmental relation, autonomy, responsibility and accountability, 100 key informants were selected based on stratified random sampling representing at least 30 sample from each municipality covering equal proportion of key informants from both public and local representative of the study area. The results are analyzed descriptively. The study found that local governments lack sufficient authority to make financial decisions (54 %) and lack adequate resources (41 %). Fiscal responsibility transfers are found will-structured. Coordination between government levels is found effective. Autonomy has improved and operate transparently. There is found high public participation in decision making. Fiscal decentralization is seen as a tool to enhance service delivery and reduce inequality. However, the study found institutional barriers and resource constraints. Lastly, the results of the study have synthesized to formulate policy recommendations and disseminated to the concerned authorities of the sample area. This study will helpful for government and further researchers.